Information Environment as a Factor of Social Situation in Development of a Modern Child - A. D. Andreyeva (Научный диалог, 2018)
The article is devoted to the analysis of the information environment of modern society, which determines the peculiarity of the social situation of the children development in the XXI century. It is shown that the information technologies in medicine play a positive role in the family's adaptation to the emergence of children, contribute to the formation of psychological readiness of parents to accept the individual characteristics of a child even before his birth. The ambiguous influence of the information environment and communication technologies on the formation of models of parental behavior is emphasized, deepening the gap between generations, destroying the continuity of family traditions and the experience of raising children, reducing the sense of responsibility for the safety of children. The risks of the current social situation of the child's development, caused by the penetration of information technologies into the daily life of a person are identified. Priority is the reduction of time and impoverishment of the content of direct communication between the adult and the child, as well as the filling of the child's playing and social space with the information environment. The question is raised about the influence of information technologies in education and new methodological possibilities on the cognitive and personal development of a modern child. It is noted that communication in social networks, which occupies a dominant position in the social interaction of adolescents, conceals the danger of weak development of reflexive abilities, the formation of distorted self-esteem, the emergence of protective psychological mechanisms.